2021
DOI: 10.13189/ujar.2021.090403
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Climate Change Impacts on Agribusiness Value Chain in Nigeria

Abstract: This paper aims to review the impact of climate change on Nigeria's agribusiness value chain. In this study, the researcher reviewed recent and popular academic journals in the area of climate change and agricultural value chains. This review process aims to strengthen the existing literature in this field of study. After carefully reviewing the literature, the paper revealed that the change in the global climate has a significant impact on the agribusiness value chain. The Nigerian agricultural value chain co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The results are consistent with studies in Economic Community of West African States exhibiting the influence of climate variables such as rainfall and temperature, and economic variables like capital and labor affects agricultural output [29]. In the same manner, it was found out that climate change in Nigeria deters the growth of the technology and manufacturing sector decreasing labor and capital productivity consequently hampering growth and sustainable development [12,34].…”
Section: Analysis Of Regression Results and Diagnostic Testssupporting
confidence: 89%
See 1 more Smart Citation
“…The results are consistent with studies in Economic Community of West African States exhibiting the influence of climate variables such as rainfall and temperature, and economic variables like capital and labor affects agricultural output [29]. In the same manner, it was found out that climate change in Nigeria deters the growth of the technology and manufacturing sector decreasing labor and capital productivity consequently hampering growth and sustainable development [12,34].…”
Section: Analysis Of Regression Results and Diagnostic Testssupporting
confidence: 89%
“…The purpose of this paper therefore, is to quantitatively evaluate how climate variability and various economic activities in agriculture affect output of Philippine agriculture. At the same time, it aims to understand the movement of climatic indicators such as temperature, precipitation, number of typhoons that hit landfall, carbon emissions, el niño and la niña in the last thirty-four (34) years in so far as the Philippines is concerned; and understand the movement of economic factors such as agricultural credit, agricultural expenditure, employment in agriculture and land area devoted in agriculture in the last thirty-four (34) years as well. Furthermore, it aims to find a causal link between agricultural production in the Philippines and the aforecited climatic indicators in particular.…”
Section: Introductionmentioning
confidence: 99%
“…al., 2022). (Sam, 2021;Ikhile, 2015). Invasive weeds, pests and fungi are part of climate change effects affecting crop yields, they thrive in warmer temperatures, increased carbon dioxide levels and wetter climates.…”
Section: Climate Change and Agriculturementioning
confidence: 99%
“…Still, perhaps the duration of direct wetting on the host surface facilitates infection, or rain splash helps the release of spores from summer/winter spores in the soil, which affects cancer development. A study showed that the rise in temperature has a negative effect, while rainfall change exerts a positive impact on agricultural productivity [9]. Previous study also considered the maximum progress and spread of infection during the rainy season in pink cancer cases [8].…”
Section: Introductionmentioning
confidence: 99%